Factors Associated with Low Birth Weight Incidence - Dimpu Rismawaty Nainggolan; Bety Mayasari; Dian Fitra Arismawati (CV. Get Press Indonesia, 2025)
Low Birth Weight (LBW) is an important indicator of newborn health and the quality of maternal care. This study aims to analyze the relationship between maternal age, parity, and gestational age with the incidence of LBW in Padang City. This study used a case-control design with a sample of 110 mothers from September to June 2022 at Adnan WD Regional General Hospital divided into case (LBW) and control (non-LBW) groups. Data were collected secondary from medical records and analyzed using the Chi-Square test. The research findings indicate that maternal age <20 years and >35 years, as well as high parity (≥4 times), are associated with a higher likelihood of LBW, although this association is not statistically significant (p>0.05). Premature gestational age also shows a tendency toward LBW, but this is not significant (p=0.061). The researcher's observations indicate that maternal age, parity, and gestational age are influenced by health conditions and access to prenatal services, while maternal nutritional status plays a significant role in fetal growth. Researchers concluded that comprehensive health interventions, including nutritional education and optimal prenatal monitoring, are needed to reduce the incidence of LBW.